Herbicide alternatives in boreal and northern temperate forests of Ontario and Quebec: A compendium of studies - K. Chapman; N. Thiffault; D. Gouge; H.D. Deighton; I. Allen; F.W. Bell; C.B. Edge; R.L. Fleming; D. Flood; M.K. Hoepting; G.J. Kayahara; C. McDonell; et al. (The Forestry Chronicle, 2024)
There is increasing concern across Canada regarding the use of chemical herbicides in forestry. In Quebec, the use of herbicides for forest management on public lands has been discontinued since 2001, and there is mounting pressure to eliminate or greatly reduce their use in Ontario. To this end, we present a digital compendium of studies that assess the medium to longer-term effectiveness of a range of vegetation management treatments in boreal and northern temperate forests of Ontario and Quebec, Canada. For inclusion, studies must have: (1) followed responses for five years or longer, or been a component of a larger project that did so; (2) included at least one silvicultural experiment type (i.e., harvest, site preparation, regeneration and/or tending); (3) included tree or other vegetation-related metrics as response variable(s); and (4) been located in or relevant to boreal or northern temperate forests of Ontario and Quebec. We classified study sites using a bioregional ecological framework that reflects site, substrate and overstory and understory vegetation characteristics relevant to vegetation management. The finalized compendium is open-access and can be used to synthesize knowledge on the silvicultural effectiveness of various herbicide alternatives, assess knowledge gaps, and identify candidate sites for re-measurement.